1955
DOI: 10.1152/ajplegacy.1955.181.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Unit Activity of Rabbit Hippocampus

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1957
1957
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…reach the hippocampus and the amygdala by fibers coming from neurons in the brain reticular formation and/or VTA, which receive connections carrying sensory information from collaterals of the diverse sensory pathways; in turn, their projections to hippocampus and amygdala via entorhinal cortex (FIGURE 4) (241) make limbic structures and basal ganglia "polysensory" and thereby able to play a role in learning, as was postulated in the 1950s (100, 218,370,592). No doubt, the ascending noradrenergic fibers that originate in the locus coeruleus and innervate the hippocampus and the amygdala and are very much involved in the generation of emotional arousal (34) and arousal-related "states" (75) must play an essential role.…”
Section: The Circuits Of Fear and Fear Extinctionmentioning
confidence: 95%
See 1 more Smart Citation
“…reach the hippocampus and the amygdala by fibers coming from neurons in the brain reticular formation and/or VTA, which receive connections carrying sensory information from collaterals of the diverse sensory pathways; in turn, their projections to hippocampus and amygdala via entorhinal cortex (FIGURE 4) (241) make limbic structures and basal ganglia "polysensory" and thereby able to play a role in learning, as was postulated in the 1950s (100, 218,370,592). No doubt, the ascending noradrenergic fibers that originate in the locus coeruleus and innervate the hippocampus and the amygdala and are very much involved in the generation of emotional arousal (34) and arousal-related "states" (75) must play an essential role.…”
Section: The Circuits Of Fear and Fear Extinctionmentioning
confidence: 95%
“…The sensory-related information from hippocampus and BLA presumably originates in the mesencephalic reticular formation and ventral tegmental area (VTA), which receive it, in turn, from collaterals of the sensory pathways (100, 218,370,592).…”
Section: Hippocampus Amygdala Infralimbic Ventromedial Prefrontmentioning
confidence: 99%
“…receive a large input from the fimbria suggests that the source of this input is the hippocampus (Raisman et al 1966). There is plentiful evidence that the hippocampus receives polysensory inputs (Green & Machne, 1955;Segal, 1974) (Beach, 1942;Heimer & Larsson, 1967). Also, sexual behaviour deficits following total hippocampal lesions (Dewsbury et al 1968) are not nearly as severe as those following similar lesions of the c.m.a.…”
Section: Resultsmentioning
confidence: 99%
“…* * Most of these studies report that sensory stimuli have a non-specific arousing effect on hippocampal neurones, usually of rather long latency ( > 100 ms.) Evidence for more specific sensory responses has been reported in four studies (Brown and Buchwald 1973, Green and Machne 1955, Molnar and Arutyunov 1969, Segal 1974). In the first of these, Green and Machne (1955) found that while many hippocampal units in the paralysed, unanaesthetized rabbit were multi-modal, activated by all the sensory stimuli that they tried, others could only be excited by one stimulus such as a touch on a particular part of the body and not by visual or auditory stimuli. There was no obvious tendency for units responsive to the same stimuli to cluster into anatomically discrete areas.…”
mentioning
confidence: 90%
“…* Studies on the activity of single hippocampal neurones in response to sensory stimulation or during motor behaviour have been published from nine laboratories (Brown and Buchwald 1973, Feder and Ranck 1973, Green and Machne 1955, Lidsky, Levine, and MacGregor 1974a,b, Molnar and Arutyunov 1969, O'Keefe 1976, O'Keefe and Dostrovsky 1971, Ranck 1973, Segal 1974, Vinogradova 1970, Vinogradova, Semyonova, and Konovalov 1970, Yokota, Reeves, and MacLean 1970. * * Most of these studies report that sensory stimuli have a non-specific arousing effect on hippocampal neurones, usually of rather long latency ( > 100 ms.) Evidence for more specific sensory responses has been reported in four studies (Brown and Buchwald 1973, Green and Machne 1955, Molnar and Arutyunov 1969, Segal 1974). In the first of these, Green and Machne (1955) found that while many hippocampal units in the paralysed, unanaesthetized rabbit were multi-modal, activated by all the sensory stimuli that they tried, others could only be excited by one stimulus such as a touch on a particular part of the body and not by visual or auditory stimuli.…”
mentioning
confidence: 99%